A determination of the effect of changing collector chain length under varying Water Quality - Natalia Sinjani, Taonga Mchirwa (Department of Chemical Engineering, 2025)
The mineral processing industry needs to recycle process wastewater to decrease the detrimental effects of its discharge into the environment. This is of high importance in regions where water availability is restricted. Recycling process water leads to differences in water quality such as changes in pH, ionic strength (IS), and the concentration of total dissolved solids (TDS). The froth and pulp zones in the flotation cell work interactively to recover minerals and changes to water quality affect both zones. The factors affect the behavior of minerals and chemical reagents, impacting flotation performance. According to literature, collector behavior can be impacted differently by certain ions. An increase in the IS and TDS of water can result in a decrease in mineral recoveries and grades. This is due to gangue and ions that either coat or create precipitates that passivate mineral surfaces, preventing collector adsorption. However, it is also known ions are capable of activating valuable minerals and gangue. Anincrease in collector chain length leads to an increase in the strength of the collector due to an increase in hydrophobicity. However, this order of strength may be affected by pH and IS as these affect the collector adsorption. The selectivity of collectors increases with a decrease in the collector chain length. pH also affects the selectivity of collectors as an increase in pH results in a decrease in grade. However, the stability of collectors is independent of chain length. A high collector dosage may not imply an increase in flotation performance as there is a risk of over-dosage. This may result in other reagents being overpowered in the pulp, leading to decreases in grades and recoveries. The first objective of this study was to investigate the differences in flotation performance when collectors of different chain lengths are used in synthetic plant water with increasing ionic strength. The second objective was to determine the interactive effects between collector chain length, collector dosage, and ionic strength of synthetic plant water on flotation performance. To address the objectives, a two-phase factorial design of experiments was created, with Phase one utilising SEX and Phase two, SIBX. The factors selected for investigation were the collector chain length, dosage and the ionic strength of synthetic plant water. Batch f lotation on a Merensky ore was utilised to obtain copper and nickel grades and recoveries which illustrated flotation performance. Additionally, batch flotation was used to obtain the entrainment factors of the two collectors at the different ionic strengths of SPW. Zeta potential measurements on chalcopyrite were utilised to determine changes to the mineral surface potential when the factors were varied. Sedimentation tests on the tails samples of the batch flotation tests provided information on the behaviour of the fines, and UV/Vis spectroscopy determined the concentration of residual xanthates present after flotation. i The study found that the longer chained collector, SIBX, behaved atypically to what has been observed in other studies. It obtained lower solids and recoveries than SEX in water with low ionic strengths. Furthermore, under these conditions, SIBX achieved the highest copper and nickel grades. Interestingly, as the ionic strength of the water increased, the trend was reversed. The copper recoveries were independent of the changes made to all the factors, however, the nickel recoveries did show slight variations. Both an increase in the ionic strength and collector chain length resulted in a decrease in the entrainment factor. Additionally, an increase in the ionic strength resulted in a less negative zeta potential. It was determined that there were interactive effects among the factors that were varied and concluded the factor with the largest impact on the flotation response (i.e. solids and water recovery and the recovery and grades of copper and nickel) was the ionic strength of the water. These conclusions emphasise the importance of investigating the effects of recirculating water within the flotation process. The determination of the effects on flotation performance by different collectors under varying water quality will provide more knowledge into the optimisation of reagent usage in mineral processing in the presence of recycled water. Subsequently, this will provide plant operators with more control over the performance of the process as reagent control may compensate for changes in water quality.